Leadless pacemaker implementation at the right atrial appendage apex: An initial preclinical assessment - Lin, Yu‐Sheng; Wu, Lung‐Sheng; Ho, Wan‐Chun; Lai, Chao‐Sung; Su, Wilber; Chu, Pao‐Hsien (Pacing and clinical electrophysiology, 2024)
Objective This study evaluates the feasibility and efficacy of implanting a leadless pacemaker at the right atrial appendage (RAA) in a preclinical minipig model, aiming to address the limitations of atrial pacing with current leadless devices like the Medtronic Micra, which is typically used for right ventricular implantation. Methods Four minipigs, each with a median body weight of 45.8 ± 10.0 kg, underwent placement of the Micra transcatheter pacing system (TPS) via the right femoral vein into the RAA apex. The pacing performance was assessed over 1‐week (short‐term) and 3‐month (long‐term) periods. Outcomes The initial findings indicated successful implantation, with satisfactory intrinsic R‐wave amplitudes and pacing threshold. In the following period, the sensitivity, threshold, and impedance were stable with time. Notably, upon explanation at 3 months, a deep myocardial penetration by the device was observed, necessitating a redesign for safe long‐term use in a growing subject's heart. Conclusion While initial results suggest that RAA apex placement of the Micra TPS is promising for potential inclusion in a dual‐chamber pacing system, the issue of myocardial penetration highlights the need for device redesign to ensure safety and effectiveness in long‐term applications.